Genetic divergence of exotic inbred lines of maize (Zea mays. L) (Bangladesh Journal of Agricultural Research, 2018)
Sixty exotic inbred lines of maize from CIMMYT were characterized for a few morphological attributes and grain yield at the experimental field of Bangladesh Agricultural Research Institute (BARI) during 2013-14. The inbred lines of the existing investigation were grouped into five distinct non-overlapping clusters based on D2 analysis. Cluster II was comprised of the highest number of inbreds whilst cluster III and IV included the lowest number of inbreds. The inter cluster distance was higher than intra cluster distance suggesting wider genetic diversity among the genotypes of different groups. The highest inter-cluster distance was exhibited between clusters II and V (D2 = 15.40) and the lowest inter-cluster distance was observed between clusters I and II (D2 = 2.82). Cluster II exhibited the highest mean values for cob length and cob diameter, cluster V for number of grain /cob and total grain weight. The lowest mean value for plant height & ear height were found in cluster II and cluster IV for days to pollen shedding and days to silking. Days to silking, plant height, cob length (cm), number of rows /cob, number of grains /cob showed maximum contribution towards total divergence among different characters. The inbred lines were characterized for their morphological traits and kernel yield to achieve more heterotic partners to get higher heterosis.Bangladesh J. Agril. Res. 42(4): 665-671, December 2017